Perancangan Sistem Informasi Pembayaran Sumbangan Pembinaan Pendidikan Studi Kasus pada SMK Putra Perdana Indonesia - Septa Petriansyah; R. Wahyudi Darmawan (DPPM Universitas Pelita Bangsa, 2022)
Currently, an information system in the field of education has developed that handles tuition payments. Tuition payments are very important in helping the needs of students and teachers. To support the committee's payment system, a computerized system that is more accurate, fast and efficient is needed. However, in reality this is sometimes not in accordance with the wishes and expectations to be achieved due to the limitations of the system. SMK Putra Perdana Indonesia Kab. Tangerang in processing committee payment data carried out by Putra Perdana Indonesia SMK Tangerang is still using the manual method, which is recorded in the ledger and only making receipts for tuition payments using a simple application, namely Microsoft Excel. The purpose of the research conducted by the author is to make an SPP payment system at SMK Putra Perdana Indonesia Kab.Tangerang using Visual Basic 2008 programming language, Unified Modeling Language (UML) and MySQL database. In addition, a new database system can also be generated that can be used as operational activities, especially the financial division. So the author took the title of the research, namely